AN EXPERT SYSTEM FOR EARTHQUAKE PREDICTION - Masyuk S.M.; Kushnir G.S. (My University, 2000)
Considerable experience in earthquake prediction has been accumulated in seismology. Numerous prediction techniques based on combinations of precursors have been developed (e.g., maps of expected earthquakes, RTL, M8, CN (California-Nevada) etc.) and are being refined and debugged using real data. The present paper is an attempt at systematizing this experience within the framework of an expert system (ES), so that forecasts can be derived based on a set of precursors. Previous prediction techniques can be regarded as decision rules in the system. This expert system will help to automatize the work of an expert in testing and modifying prediction rules and techniques based on selected sets of geophysical parameters.